2022
DOI: 10.1142/s0218539321500479
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Complex System Under the k-out-of-n: G Type Configuration with k Consecutive Degraded States through the Copula Repair Approach

Abstract: This paper is the stochastic analysis of a complex repairable system comprising of subsystems in a series arrangement under the [Formula: see text]-out-of-[Formula: see text]: [Formula: see text] type configuration. Both of the subsystems are in series arrangement and having auto transfer switches when some unit fails. Subsystem 1 is supposed to work under the [Formula: see text]-out-of-[Formula: see text]: [Formula: see text], scheme, and subsystem 2 which has four indistinguishable units in parallel arrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…investigated the covariance and reliability of weighted K ‐out‐of‐ n MSSs. Recently, the coupla approach has been used in reliability estimation of repairable k ‐out‐of‐ n systems 10–14 . In general, UGF technique and recursive methods are used to estimate reliability indices of weighted system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…investigated the covariance and reliability of weighted K ‐out‐of‐ n MSSs. Recently, the coupla approach has been used in reliability estimation of repairable k ‐out‐of‐ n systems 10–14 . In general, UGF technique and recursive methods are used to estimate reliability indices of weighted system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the coupla approach has been used in reliability estimation of repairable k-out-of-n systems. [10][11][12][13][14] In general, UGF technique and recursive methods are used to estimate reliability indices of weighted system. Further, in the aforementioned research work, the system considered were binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…Poonia et al [15] used the copula repair approach to examine the performance of a warm standby k-out-of-n: G and 2-out-of-4: G system. Singh et al [22] reported a reliability assessment of a multi-computer system with n clients and the k-out-of-n: G operation scheme with copula repair policy.To analyze the availability of the butteroil production system, Mehta et al [31] developed a mathematical model that took into account the reliability of each subsystem and the system as a whole. The model also considered the time required for repair and maintenance of the subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…Such literatures present different types of system architectures employing the k-out-of-n: G scheme in form of standby, series or parallel configurations. Motivated by the work ofPoonia and Sirohi [14], Poonia et al [21], Singh and Ram [19], Singh and Gahlot [20], Singh et al [21] and Singh et al [22], in which the system design consisting of only one subsystem with a k-out-of-n: G operational scheme. Little is known on performance evaluation of serial system consisting of two subsystems in which each subsystem possesses n units working under k-out-of-n: G scheme attended by a controller whose error can lead to system failure.…”
Section: Introductionmentioning
confidence: 99%